A cementitious material admixture composition and hydraulic lime mortar

CN115583823BActive Publication Date: 2026-10-27CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211289603.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2026-10-27
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

[0007]本发明的目的是针对目前砖石古建筑文物修缮和加固所用的NHL修复砂浆耐久性能不足的问题,提供一种胶凝材料外加剂组合物以及使用该外加剂组合物制备的高耐久性水硬性石灰砂浆,本发明的石灰砂浆具有低收缩、适中的强度和高耐环境侵蚀性能,与砖石相容性好,能够满足古建筑修缮的性能和兼容性要求,可应用于砖石古建筑文物的修复和加固工程

Benefits of technology

[0049]1.本发明的外加剂组合物中的聚羧酸减水剂可以改善石灰砂浆的流动度;吸水树脂则通过其内养护方式,在硬化过程中释放水分,克服了硬化后砂浆内部水分的快速蒸发进而发生干燥收缩导致的砂浆结构稳定性下降的问题,在不增大水胶比的前提下,提高了砂浆结构的稳定性;甲基硅酸钠和亚铁氰化钾的使用,分别从防水角度和抑制侵蚀性盐分在砂浆内部结构聚积结晶从而造成结构破坏两个方面,提升了天然水硬性石灰砂浆的耐侵蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003900868070000061
    Figure BDA0003900868070000061
  • Figure BDA0003900868070000071
    Figure BDA0003900868070000071
  • Figure BDA0003900868070000072
    Figure BDA0003900868070000072
Patent Text Reader

Abstract

The present application provides a cementing material additive composition, which comprises a water reducing agent, a water absorbing resin, sodium methyl silicate and potassium ferrocyanide. The present application also provides a hydraulic lime mortar containing the additive composition and a preparation method thereof. The lime mortar of the present application has high environmental erosion resistance and can be used as a repair material for ancient buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials and cultural relic protection materials, specifically to a high-durability natural hydraulic lime mortar, its preparation method, and its application. Background Technology

[0002] Ancient architectural sites are exposed to the natural environment for a long time throughout history, and are subject to erosion and damage from the environment (physical, chemical and biological weathering), air pollution and human damage. The physical and chemical erosion reactions cause varying degrees of damage to both the interior and exterior of the base material. Most cultural relics have varying degrees of damage such as local cracking, surface peeling or even complete collapse.

[0003] In my country, most ancient brick and stone buildings use lime as a cementing material. Adhering to the principle of restoring the old as it was, lime-based repair materials are still preferred in restoration. However, air-hardening lime has low early strength, slow setting and hardening, poor volume stability and water resistance, and is prone to decomposition and collapse in humid or underwater environments, resulting in unsatisfactory performance. In recent years, the successful application of natural hydraulic lime (NHL) as a repair base material in ancient building restoration projects (such as the Jinshui Bridge of the Forbidden City, the Ancient City of Pingyao, and the Zhaozhou Bridge of the Sui Dynasty) has enabled better preservation of the cultural value of these ancient buildings.

[0004] NHL (Nephrite Hydrocarbonate) is produced by calcining and smelting clayey or siliceous limestone. Its mineral phase consists of dicalcium silicate, calcium hydroxide, and a small amount of calcium carbonate. It is an inorganic cementing material that combines hydraulic and air-hardening properties. Due to the inherent properties of NHL and the specific environment in which it is used, its durability is the primary indicator of its repair value. However, research on the environmental erosion of NHL-based materials shows that their performance deteriorates significantly in extreme corrosive environments, such as a substantial reduction in mechanical strength and the formation of noticeable cracks. Therefore, the long-term effectiveness of repair methods using NHL as the base material needs careful consideration.

[0005] The various natural environments surrounding the brick / stone / rock and earthen ancient buildings and mural ruins contain different forms of salt compounds, and their salt damage is closely related to salt activity and environmental changes within the ruins. Sulfuric acid rain caused by modern industrial development has accumulated in the soil and building foundations over a long period, resulting in sulfates that cause severe erosion and damage to the ancient building foundations, including NHL-repairable materials.

[0006] Therefore, it is essential to develop NHL-based materials with high durability so that the masonry and stone masonry building bases can be protected for a long time after repair and reinforcement. Summary of the Invention

[0007] The purpose of this invention is to address the problem of insufficient durability of NHL repair mortar used in the current repair and reinforcement of ancient brick and stone buildings. This invention provides a cementitious material admixture composition and a high-durability hydraulic lime mortar prepared using this admixture composition. The lime mortar of this invention has low shrinkage, moderate strength, and high resistance to environmental erosion. It also has good compatibility with brick and stone, meeting the performance and compatibility requirements for the repair of ancient buildings. It can be applied to the repair and reinforcement of ancient brick and stone buildings.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a cementitious material admixture composition comprising a water-reducing agent, a water-absorbing resin, sodium methylsilicate, and potassium ferrocyanide.

[0010] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to water-reducing agent is (0.2-1.5):(0.2-1.2), preferably (0.5-1.2):(0.5-1.0), and more preferably (0.7-1.0):(0.5-0.8).

[0011] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to water-reducing agent is 1:(0.15-6), preferably 1:(0.4-2), and more preferably 1:(0.5-1.2).

[0012] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to water-absorbing resin is (0.2-1.5):(0.05-0.2), preferably (0.5-1.2):(0.08-0.15), and more preferably (0.7-1.0):(0.08-0.12).

[0013] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to water-absorbing resin is 1:(0.03-1), preferably 1:(0.06-0.3), more preferably 1:(0.08-0.2).

[0014] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to sodium methylsilicate is (0.2-1.5):(0.5-1.5), preferably (0.5-1.2):(0.8-1.2), and more preferably (0.7-1.0):(0.9-1.1).

[0015] According to some embodiments of the present invention, in the composition, the mass ratio of potassium ferrocyanide to sodium methylsilicate is 1:(0.3-7.5), preferably 1:(0.6-2.5), and more preferably 1:(0.9-1.6).

[0016] According to some embodiments of the present invention, in the composition, the mass ratio of water-reducing agent, water-absorbing resin, sodium methylsilicate and potassium ferrocyanide is (0.2-1.2):(0.05-0.2):(0.5-1.5):(0.2-1.5).

[0017] According to some embodiments of the present invention, the water-reducing agent includes a polycarboxylate water-reducing agent.

[0018] According to some embodiments of the present invention, the water-reducing agent is selected from one or more of polyester-based polycarboxylate high-performance water-reducing agents, polyether-based polycarboxylate high-performance water-reducing agents, amide / imide-type polycarboxylate water-reducing agents, and amphoteric polycarboxylate water-reducing agents (polyamide-polyethylene glycol branched water-reducing agents).

[0019] According to some embodiments of the present invention, the water-reducing agent is a 540P type polycarboxylate water-reducing agent.

[0020] According to some embodiments of the present invention, the solid content of the water-reducing agent is >95%.

[0021] According to some embodiments of the present invention, the water-absorbing resin is a superabsorbent resin. In some embodiments, the water-absorbing resin is selected from one or more of polyacrylate, starch acrylate polymer, starch-acrylonitrile graft copolymer, and acrylamide-acrylonitrile-acrylic acid terpolymer.

[0022] According to some embodiments of the present invention, the water absorption ratio of the water-absorbing resin is 30 to 50 times, for example 35 times, 40 times, 45 times, etc.

[0023] In a second aspect, the present invention provides a hydraulic lime mortar comprising cementitious materials, aggregates, water, and an admixture composition as described in the first aspect of the present invention, or prepared from raw materials comprising cementitious materials, aggregates, water, and an admixture composition as described in the first aspect of the present invention.

[0024] According to some embodiments of the present invention, the cementing material includes natural hydraulic lime, mineral powder and silica fume.

[0025] In this invention, mineral powder and silica fume are both highly active pozzolanic materials. They react with calcium hydroxide in natural hydraulic lime to form partially hydrated calcium silicate (aluminate), thereby improving the stability of the cemented skeleton structure. While obtaining better mechanical properties, it can also improve the corrosion resistance of the internal structure.

[0026] In some embodiments, the mineral powder is S95 grade mineral powder.

[0027] In some embodiments, the particle size of the silica fume is 0.1–5 μm.

[0028] According to some embodiments of the present invention, the content of natural hydraulic lime in the cementitious material is 60wt% to 90wt%, for example 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%, preferably 65wt% to 85wt%, more preferably 70wt% to 80wt%.

[0029] According to some embodiments of the present invention, the content of mineral powder in the cementitious material is 5wt% to 25wt%, for example 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt% or 25wt%, preferably 10wt% to 20wt%, more preferably 15wt% to 20wt%.

[0030] According to some embodiments of the present invention, the silica fume content in the cementitious material is 1wt% to 20wt%, for example 1wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt% or 20wt%, preferably 5wt% to 15wt%, more preferably 5wt% to 10wt%.

[0031] According to some embodiments of the present invention, the cementitious material contains 60wt% to 90wt% natural hydraulic lime, 5wt% to 25wt% mineral powder, and 1wt% to 20wt% silica fume.

[0032] According to a preferred embodiment of the present invention, the cementitious material contains 65wt% to 85wt% natural hydraulic lime, 10wt% to 20wt% mineral powder, and 5wt% to 15wt% silica fume.

[0033] According to a more preferred embodiment of the present invention, the cementitious material contains 70wt% to 80wt% natural hydraulic lime, 15wt% to 20wt% mineral powder, and 5wt% to 10wt% silica fume.

[0034] In the admixture composition of this invention, the water-absorbing resin can absorb some moisture during mixing. As hardening progresses, it migrates to the matrix, increasing relative humidity and achieving internal curing to reduce drying shrinkage. Sodium methylsilicate has good penetrating crystallization properties, providing good waterproofing. Potassium ferrocyanide, as an anti-caking agent, can effectively prevent external salts from accumulating and crystallizing inside the matrix of ancient building materials, thus preventing crystallization pressure damage.

[0035] According to some embodiments of the present invention, the amount of the water-reducing agent is 0.2% to 1.2% of the total weight of the cementitious material, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, etc., preferably 0.5% to 1.0%, more preferably 0.5% to 0.8%.

[0036] According to some embodiments of the present invention, the amount of the water-absorbing resin accounts for 0.05% to 0.2% of the total weight of the cementitious material, for example 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%, preferably 0.08% to 0.15%, and more preferably 0.08% to 0.12%.

[0037] According to some embodiments of the present invention, the amount of sodium methylsilicate used accounts for 0.5% to 1.5% of the total weight of the cementitious material, for example 0.5%, 0.6%, 0.7%, 0.75%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4% or 1.5%, preferably 0.8% to 1.2%, more preferably 0.9% to 1.1%.

[0038] According to some embodiments of the present invention, the amount of potassium ferrocyanide is 0.2% to 1.5% of the total weight of the cementitious material, for example 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, preferably 0.5% to 1.2%, more preferably 0.7% to 1.0%.

[0039] According to some embodiments of the present invention, the aggregate comprises quartz sand, preferably, the fineness modulus Mx of the quartz sand is 2.3 to 3.0, more preferably 2.5 to 3.0.

[0040] According to some embodiments of the present invention, the weight ratio of the aggregate to the cementitious material is (1-3):1, preferably (1-2):1. In some embodiments, the weight ratio of the quartz sand to the cementitious material is (1-3):1, preferably (1-2):1.

[0041] According to some embodiments of the present invention, the weight ratio of water to the cementitious material is (0.5-0.6):1, preferably (0.52-0.58):1.

[0042] This invention is based on the water content requirements for mortar in the European standard BS EN 459. The water-cement ratio is selected to be 0.5 to 0.6, which ensures that the mortar has basic workability while keeping its pore structure from changing significantly and ensuring that the mortar has good air permeability.

[0043] Thirdly, the present invention also provides a method for preparing the lime mortar described in the second aspect, comprising the step of mixing the cementitious material with aggregate, water and the admixture composition to obtain the lime mortar.

[0044] According to some embodiments of the present invention, the preparation includes the following steps:

[0045] (1) The admixture composition is mixed with water to obtain an aqueous admixture solution;

[0046] (2) The admixture aqueous solution is mixed with the cementitious material and aggregate to obtain the lime mortar.

[0047] Fourthly, the present invention provides the application of the lime mortar described in the second aspect or the lime mortar prepared by the method described in the third aspect in the restoration of ancient buildings.

[0048] The beneficial effects of this invention are:

[0049] 1. The polycarboxylate superplasticizer in the admixture composition of the present invention can improve the fluidity of lime mortar; the water-absorbing resin releases water during the hardening process through its internal curing method, overcoming the problem of rapid evaporation of water inside the hardened mortar and subsequent drying shrinkage leading to a decrease in the stability of the mortar structure, thus improving the stability of the mortar structure without increasing the water-cement ratio; the use of sodium methylsilicate and potassium ferrocyanide improves the erosion resistance of natural hydraulic lime mortar from two aspects: waterproofing and inhibiting the accumulation and crystallization of corrosive salts in the internal structure of the mortar, thereby preventing structural damage.

[0050] 2. The mineral powder and silica fume used in this invention are widely available, inexpensive, and do not corrode or cause secondary damage to cultural relics. The use of both can improve the performance of NHL, reduce the cost of ancient building restoration materials, and also have certain low-carbon benefits.

[0051] 3. This invention obtains a highly durable natural hydraulic lime mortar by using a cementitious material additive composition and inorganic active minerals (mineral powder and silica fume), which can be used for the protection of ancient brick and stone buildings and cultural relics in harsh environments. Detailed Implementation

[0052] The technical solutions in the embodiments of the present invention will be described in detail below with reference to specific embodiments and comparative examples. The embodiments described are only some embodiments of the present invention, and not all of them.

[0053] Reagent composition or brand:

[0054] Natural hydraulic lime: NHL2, 28-day strength 2-7 MPa, manufactured by Saint-Astier, France;

[0055] Mineral powder: Granulated blast furnace slag powder, with an activity grade of S95, purchased from Tangshan Iron and Steel Group Co., Ltd.;

[0056] Silica fume: particle size 0.1-5μm, purchased from Yinchuan Steel Plant, Ningxia;

[0057] Polycarboxylate superplasticizer: solid content > 95%, White powder with a bulk density of 0.6 ± 0.1 g / cm³ 3 pH 10.5±0.5 (23℃, 40% solution), purchased from Sika Company;

[0058] Super absorbent resin: with a water absorption rate of approximately 40 times;

[0059] Quartz sand: fineness modulus Mx 2.9.

[0060] The methods for preparing lime mortar in the various embodiments and comparative examples of the present invention are as follows:

[0061] (1) Add the polycarboxylate superplasticizer, superabsorbent resin, sodium methylsilicate and potassium ferrocyanide to water respectively, and stir thoroughly with a glass rod until all the components of the additive are dissolved in the water to obtain an aqueous solution of the additive.

[0062] (2) Mix NHL2, mineral powder and silica fume in a certain proportion to obtain a cementitious material;

[0063] (3) NHL2 mortar is prepared using a cement mortar mixer. First, add the admixture aqueous solution to the mixing pot, then add the mixed cementitious material to the mixing pot, add the quartz sand to the sand strainer, start the mixer, set the program to automatic mode, mix at low speed (140±5 rpm) for 30 seconds, and at the beginning of the second 30 seconds, add the quartz sand evenly. Then, switch the machine to high speed (285±10 rpm) for 30 seconds, stop mixing for 90 seconds, and use a rubber scraper to scrape the mortar from the blades and the pot wall into the middle of the pot within the first 15 seconds. Continue mixing at high speed for 60 seconds and then end the program to obtain the mixed mortar.

[0064] Example 1

[0065] This embodiment provides a lime mortar, comprising the following components:

[0066] The composition includes cementitious materials (70 wt% natural hydraulic lime, 20 wt% mineral powder, and 10 wt% silica fume), water, quartz sand, polycarboxylate superplasticizer, superabsorbent resin, sodium methylsilicate, and potassium ferrocyanide.

[0067] The mass ratio of water to cementitious material (water-cement ratio) is 0.5.

[0068] The mass ratio of cementitious material to quartz sand (cement-sand ratio) is 1:2.

[0069] The dosage of polycarboxylate superplasticizer is 0.5% of the mass of the cementitious material.

[0070] The amount of superabsorbent polymer (SAP) used is 0.1% of the mass of the cementitious material.

[0071] The amount of sodium methylsilicate used is 1% of the mass of the cementitious material.

[0072] The amount of potassium ferrocyanide used is 0.8% of the mass of the cementitious material.

[0073] Example 2-11

[0074] The specific composition and proportion (mass ratio) of the lime mortar provided in Examples 2-11 are shown in Table 1.

[0075] Comparative Examples 1-11

[0076] The specific composition and proportion (mass ratio) of the lime mortar provided in Comparative Examples 1-11 are shown in Table 1.

[0077] Table 1

[0078]

[0079]

[0080] Effect test:

[0081] The NHL mortars prepared in the examples and comparative examples were subjected to the following performance tests:

[0082] Mortar flowability: Tested according to standard GB / T-2419-2005 "Determination of Flowability of Cement Mortar";

[0083] The NHL 28-day compressive and flexural strength was tested according to the standard GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)" with mortar dimensions of 40×40×160mm.

[0084] Resistance to sodium sulfate solution corrosion: 28-day-old NHL mortar was immersed in a 5% (w / w) Na₂SO₄ solution. After 28 days of immersion, the compressive strength of the mortar was measured, and the rate of change in strength was calculated. The Na₂SO₄ solution was replaced weekly during the test. The calculation method for the rate of change in compressive strength of the mortar before and after immersion in Na₂SO₄ solution is as follows:

[0085]

[0086] In formula (1): ------Change rate of mortar compressive strength (%),**------ A positive value indicates an increase in the compressive strength of the mortar. A negative value indicates a loss of mortar compressive strength;

[0087] S0------The compressive strength (MPa) of mortar before immersion in Na2SO4 solution;

[0088] S1------The compressive strength (MPa) of mortar after soaking in Na2SO4 solution;

[0089] Freeze-thaw cycle resistance: The prepared 28-day-old NHL mortar was immersed in water and saturated for 24 hours using a vacuum saturation machine. Then, it underwent 30 freeze-thaw cycles (-20℃ to 20℃). After 30 freeze-thaw cycles, the compressive strength of the mortar was measured, and its strength change rate was calculated. The calculation method for the mortar strength change rate before and after freeze-thaw cycles is as follows:

[0090]

[0091] In formula (2): η**------the strength change rate of mortar (%),**------η is a positive value indicating an increase in the strength of the compressive mortar, and η is a negative value indicating a loss of the compressive strength of the mortar;

[0092] F0------The compressive strength of the mortar before freeze-thaw cycles (MPa);

[0093] F1------The compressive strength of mortar after freeze-thaw cycles (MPa);

[0094] Mortar drying shrinkage test: The mortar was molded in a 40×40×160mm steel mold, and after 3 days the mold was removed. The change in the length of the sample was measured using a universal projection length measuring instrument, and its 28-day drying shrinkage rate was calculated.

[0095] Waterproofing test: The waterproofing performance of mortar is characterized by its water absorption rate, and the test is conducted in accordance with the standard JGJ-T 70-2009 "Mortar Test Method".

[0096] The relevant performance test results are shown in Table 2.

[0097] Table 2

[0098]

[0099]

[0100] As can be seen from the results of Example 2 and Comparative Examples 3-4 and 10-11, when the admixture composition of the present invention contains four substances simultaneously: water-reducing agent, water-absorbing resin, sodium methylsilicate and potassium ferrocyanide, the resulting natural hydraulic lime mortar exhibits excellent performance in terms of fluidity, 28-day compressive strength, resistance to sulfate and freeze-thaw cycle erosion, drying shrinkage and water absorption.

[0101] As can be seen from the results of Example 2 and Comparative Examples 6-8, the cementitious material of the present invention contains lime mortar prepared from natural hydraulic lime, mineral powder and silica fume, which can not only improve the 28-day compressive strength and the ability to resist sulfate and freeze-thaw cycle erosion, but also reduce the drying shrinkage rate and water absorption rate.

[0102] In summary, by using the admixture composition of the present invention and combining it with the addition of inorganic active minerals, NHL mortar can significantly improve its resistance to sulfate and freeze-thaw cycles while ensuring good workability. At the same time, its volume (structural) stability is also significantly enhanced, indicating that it has high durability in the harsh northern environment (high salt erosion and low temperature freeze-thaw). This ensures that the NHL mortar of the present invention can resist environmental damage when applied to the restoration and reinforcement of ancient building and cultural relic substrates.

[0103] The embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the terms used herein are descriptive and explanatory, not limiting. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from its scope and spirit. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications having the same function.

Claims

1. A hydraulic lime mortar, comprising a composition of cementitious materials, aggregates, water and cementitious material admixtures, or prepared from raw materials comprising a composition of cementitious materials, aggregates, water and cementitious material admixtures; The cementitious material admixture composition includes a water-reducing agent, a water-absorbing resin, sodium methylsilicate, and potassium ferrocyanide; The cementing material includes natural hydraulic lime, mineral powder, and silica fume; The cementitious material contains 65wt% to 85wt% natural hydraulic lime, 10wt% to 20wt% mineral powder, and 5wt% to 15wt% silica fume. The water-reducing agent is used at a rate of 0.5% to 1.0% of the total weight of the cementitious material; the water-absorbing resin is used at a rate of 0.08% to 0.15% of the total weight of the cementitious material; the sodium methylsilicate is used at a rate of 0.8% to 1.5% of the total weight of the cementitious material; and the potassium ferrocyanide is used at a rate of 0.5% to 1.2% of the total weight of the cementitious material.

2. The lime mortar according to claim 1, characterized in that, The water-reducing agent includes a polycarboxylate water-reducing agent; and / or the water absorption ratio of the water-absorbing resin is 30 to 50 times.

3. The lime mortar according to claim 2, characterized in that, The solid content of the polycarboxylate superplasticizer is >95%.

4. The lime mortar according to claim 1, characterized in that, The mineral powder is S95 grade mineral powder.

5. The lime mortar according to claim 1, characterized in that, The particle size of the silica fume is 0.1–5 μm.

6. The lime mortar according to claim 1, characterized in that, The amount of sodium methylsilicate used accounts for 0.8% to 1.2% of the total weight of the cementitious material.

7. The lime mortar according to claim 1, characterized in that, The aggregate includes quartz sand; And / or the weight ratio of the aggregate to the cementitious material is (1-3):1; And / or the weight ratio of the water to the cementitious material is (0.5 to 0.6):

1.

8. The lime mortar according to claim 7, characterized in that, The fineness modulus of the quartz sand is 2.5 to 3.

0.

9. The lime mortar according to claim 1, characterized in that, The weight ratio of the aggregate to the cementitious material is (1-2):

1.

10. The lime mortar according to claim 1, characterized in that, The weight ratio of water to the cementitious material is (0.52 to 0.58):

1.

11. The method for preparing lime mortar according to any one of claims 1 to 10, characterized in that, The lime mortar is obtained by mixing the cementitious material with aggregate, water and the admixture composition.

12. The preparation method according to claim 11, characterized in that, The preparation includes the following steps: (1) The admixture composition is mixed with water to obtain an aqueous admixture solution; (2) The admixture aqueous solution is mixed with the cementitious material and aggregate to obtain the lime mortar.

13. The application of the lime mortar according to any one of claims 1 to 10 or the lime mortar prepared by the method according to claim 11 or 12 in the restoration of ancient buildings.

Citation Information

Patent Citations

  • Lime-based micro-contraction grouting material composition and preparation method thereof

    CN107285718A

  • Low-shrinkage-percentage resin mineral composite cement-based material and preparation method thereof

    CN108484044A